Action learning and public health pedagogy: Student reflections from an experiential public health course - Pham, Christine N.; Cunningham, Shayna D.; Humphries, Debbie L. (Frontiers in Public Health, 2023)
Introduction Applied practice experiences are essential components of the Masters of Public Health (MPH) curriculum. The objective of this study was to examine students’ perspectives on the skills and expertise they developed in an MPH course offering applied practice opportunities. Methods Of 236 students who took the course from 2008 to 2018, email addresses were obtained for 212 and 104 completed the consent form. Following consent, reflection essays were de-identified and analyzed using a rapid qualitative analysis approach. The essays addressed students’ learning experiences and application of the competencies for MPH programs set by the Council for Education in Public Health (CEPH). Deductive and inductive analytical lenses were used to identify the key lessons learned by each cohort of students. Semi-structured guides and matrixes for essay analysis were created using assignment instructions and CEPH competencies. Results Although the reflection paper assignment varied across the years, commonalities were observed in the student reflections. Key themes included turning theory into practice, navigating the complex environment of public health practice, skill building, critical self-reflection, challenges encountered, and elements that facilitated project success. Students reported developing practical skills, such as planning for independent research (e.g., preparing for institutional review board (IRB) submission, consulting with faculty and other experts), identifying realistic approaches for data extraction during chart reviews and analyses of electronic medical records, and disseminating findings for diverse stakeholders and audiences. Students also reported strengthening cross-cutting skills such as communication, teamwork, and problem-solving that were useful for navigating power dynamics and balancing competing interests and expectations. Students explored their identity as public health professionals as they navigated the dynamics of public health practice. Conclusion The applied practice experience served as a valuable tool for knowledge and skills acquisition. Moreover, it served as an opportunity for students to engage with the unique organizational cultures of their respective community partners and to deepen their understanding the complexities of conducting meaningful community-engaged research. Implications This study demonstrates the utility of analyzing students’ critical self-reflections as a tool for exploring learning experiences when training future public health professionals. The findings can help educators design future applied practice experiences.